Description, importance and research on schedules of reinforcement: explaining personality, ordering behaviors and clarifying feelings - Costa, Carlos Eduardo; Banaco, Roberto Alves; Becker, Rodrigo Morande; Luiz, André Connor de Méo (Perspectivas em Análise do Comportamento, 2024)
Schedules of Reinforcement underlie most organism behaviors, making their profound knowledge essential for every Behavior Analyst. This article introduces positive reinforcement schedules, which every Behavior Analysis student should know. The article intends to start with the basics, targeting undergraduate and postgraduate students, but also to enable in-depth study through the numerous citations and references within this work. The article provides examples beyond the laboratory in each reinforcement program described, seeking to make the reader understand the relationship between the central theme and the construction of personality and the possible feelings engendered. It also discusses related subjects, such as contingency, motivating (or establishing) and abolishing operations, and discrete and freeoperant test procedures.